2016
DOI: 10.1073/pnas.1604600113
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous macrophage migration inhibitory factor reduces the accumulation and toxicity of misfolded SOD1 in a mouse model of ALS

Abstract: Mutations in superoxide dismutase (SOD1) cause amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease characterized by the loss of upper and lower motor neurons in the brain and spinal cord. It has been suggested that the toxicity of mutant SOD1 results from its misfolding and accumulation on the cytoplasmic faces of intracellular organelles, including the mitochondria and endoplasmic reticulum (ER) of ALS-affected tissues. Recently, macrophage migration inhibitory factor (MIF) was shown to dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 54 publications
4
58
0
Order By: Relevance
“…13.25 ± 3.05% of wild type astrocytes were positive for mHSPB1, whereas 37.40 ± 3.18% of SOD1(G93A) astrocytes were positive for mHSPB1 (Figure 2A, 2B). Co-staining, with antibodies specific to misfolded SOD1 (4751), revealed that SOD1 and mHSPB1 are visualized in the cytoplasm, and that 41.03 ± 3.25% of mHSPB1 positive astrocytes were also positive for misfolded SOD1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13.25 ± 3.05% of wild type astrocytes were positive for mHSPB1, whereas 37.40 ± 3.18% of SOD1(G93A) astrocytes were positive for mHSPB1 (Figure 2A, 2B). Co-staining, with antibodies specific to misfolded SOD1 (4751), revealed that SOD1 and mHSPB1 are visualized in the cytoplasm, and that 41.03 ± 3.25% of mHSPB1 positive astrocytes were also positive for misfolded SOD1.…”
Section: Resultsmentioning
confidence: 99%
“…The blots were then incubated with primary antibodies against human HSPB1, mHSPB1, SOD1, misfolded SOD1 or Tubulin for 1 hour at room temperature. The antibody against misfolded SOD1 has been previously described to be specific to human SOD1 under denaturing conditions and specific for mutant SOD1 isoforms under non-denaturing conditions (4751). Blots were then washed 3 times with TBS-T, and incubated with secondary antibody for 1 hour at room temperature, and then scanned using a Licor Odyssey Classic.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that MIF can inhibit the accumulation of misfolded SOD1 [36,39]. MIF can regulate both intracellular and extracellular pathways.…”
Section: Mif In Alsmentioning
confidence: 99%
“…In particular, the ability of MIF to suppress the toxicity of SOD1 misfolded in motor neuron-like cells may be due to changes in the aggregation model from amyloid aggregates to amorphous aggregates [36]. In particular, in in vitro studies, MIF chaperone activity inhibits the formation and toxicity of misfolded SOD1 amyloid aggregates, when overexpressed in neuroblastoma cell lines such as SH-SY5Y or mouse motor neuron-like hybrid cell line NSC-34 differentiable in motor neurons [36,39]. Studies in animal models of ALS have validated the potential beneficial effects of endogenous MIF [39,41].…”
Section: Mif In Alsmentioning
confidence: 99%
See 1 more Smart Citation